Lip and allar base dimensions among adolescence in healthy and post unilateral cleft lips correction in deutro-malaid population - Coen Pramono D (Dental Journal (Majalah Kedokteran Gigi), 2006)
The purpose of this study is to observe the differences between some anthropometric values of the lip and allar base area in normal and those who had undergone incomplete unilateral cleft lip surgical correction using Millard’s I technique. The investigation was done on male und female adolescence of 12–15 years of age. Thirteen anthropometric dimension variables were observed, as X1 = width of the allar base, X2 = the distance between two corners of the mouth, X3 = the distance between the center of the lip and the right mouth corner, X4 = the distance between the center of the lip and the left mouth corner, X5 = the distance between the center of the allar base and the center of the of upper lip, X6 = the distance between upper part of two philtrum pillars, X7 = the distance between two philtrum pillars base, X8 = the height of right philtrum pillar, X9 = the height of left philtrum pillar, X10 = the distance between the right allar base to the right mouth corner, X11 = the distance between the left allar base to the left mouth corner, X12 = the width of the right nostril, and X13 = the width of the left nostril. The t-test analysis showed the average of the anthropometric lip and allar base dimensions among male adolescence groups in variables of X1, X2, X4, X5, X6, X7, X10, X11, X12, and X13 shown with significant differences from those of some variables which had undergone incomplete unilateral cleft lip surgical correction (p < 0.05), and no significant differences shown in the variables of X3, X6, X8, and X9 (p > 0.05). The result of the test among the female group presented a significant difference in variables of X4, X5, X6, X9, X11, X12 and X13 (p < 0.05), differed what given in variables of X1, X2, X3, X7 and X8 showed with no significant difference (p > 0.05). It concluded that there are differences in dimensions of the lips and allar bases among normal and post-surgical groups both in adolescence males and females.